A formação para o trabalho da agricultura familiar camponesa: os limites e desafios nos processos de resistência para a produção e comercialização na cidade de Uberlândia - Fernandes, José Eduardo (2015)
Education has a crucial role, both to inculcate the hegemonic idea is a \"natural\" process of society organization by the bourgeoisie, such as to oppose, disrupt and overcome the bourgeois values by workers. Is the essence of the hegemonic capitalist process the idea that it is necessary to train, tame and instrumentalizing workers with market technical information to enable their work for producing. So education is one of the paths that point to improve the living conditions for the workers. Between alternatives, there are projects developed within university incubators to support self-managed groups of workers who want to organize ork collective work to confront the market relations and joint overcome the difficulties. From the perspective of incubation, such as carry enti-ties of knowledge transfer that act within the scope of the Solidarity Economy exercise this task of educating workers toward the construction of economic emancipation? It hypothesis of this work, the technicalities contemporary education reinforces the hege-monic idea of society (the farmer is supplier of raw materials for value addition by third parties), which limits the worker to engage in a certain role by the elites holding the capital as well such as the public entities who hold the same logic for workers, spread-ing individualism as a means of development. The general objective of this dissertation is to analyze the limits and challenges faced by a group of workers of landman family agriculture incubated in CIEPS / UFU, from the 2010s to take ownership of production and marketing through education process technologies to the work. Therefore, this work will make the exercise of prioritizing the quality of information shared in times of ad-vice made to the developments of family landman farmers, incubated in CIEPS / UFU. To make the analysis of this information is necessary to identify the realities these workers, their activities and difficulties and at the same time reflect on the hopes, disap-pointments, difficulties and problems experienced in their trajectories. The proposal to build a collective education process for CIEPS has guidance on the need to think of a logic that has two main arguments, a technique which can transfer accumulated knowledge at every possible areas of the university, which allows the appropriation of knowledge, skills and values for workers, and the other axis founded on broad policy and training that enables the formation of class consciousness, that is participatory and representative of the social struggles of the workers and that both have the link between practice and theory. Deepening the educational process and the relationship with the technical appropriation of knowledge coordinated with the political education for work-ers is still a challenge for the solidarity relations but that should can never stop be a pri-ority in the path of construction of human emancipation.